Empowering private labels through packaging : an analysis about the implementation of copycat strategies on private labels - Lisboa, Joana Rita da Fonseca Robalo (2016)
Private Labels (PLs) are an important instrument for retailers to increase their relative market power since they may increase customer loyalty, improve margins and sales and lower prices. In fact, retailers are constantly being challenged to search for methods which can leverage their own brands, namely packaging strategies. However, in order to reach its full potential, it is imperative to comprehend the real value behind the new prevalent packaging trend across PLs: Copycat packaging strategy. Hence, the present dissertation aims to analyze and understand the potential effects of PLs´ copycat packaging strategy on consumers’ perceptions toward products, assessing to what extent the adoption of this strategy triggers consumers’ purchase intention. To this end, the Portuguese retailer Sonae MC kindly provided access to the necessary data for this study. By conducting exploratory and descriptive research approaches, results revealed that the higher the level of copycat packaging on PLs, the higher the probability that PLs are perceived as being produced by the same manufacturer as National Brands (NBs), contributing to enhanced perceptions of quality. Moreover, consumers perceive copycat packaging PL’ products as being more expensive than PL’ products which follow distinct packaging strategies. Ultimately, the present dissertation demonstrates that copycat packaging strategy is a beneficial strategy that must be adopted by retailers, since it increases consumers’ purchase intention of PLs.